Newcomers Abroad: Expatriate Adaptation during Early Phases of International Assignments - Firth, Brady M.; Chen, Gilad; Kirkman, Bradley L.; Kim, Kwanghyun (Academy of Management Journal, 2014)
Integrating work from the expatriate adjustment and newcomer socialization literatures within a motivational framework, we propose that motivational states and stress cognitions impact expatriates' work adjustment patterns over time, which in turn influence important assignment attitudes. In accordance with our theorizing, analyses of longitudinal data collected from 70 expatriates during their first four months of international assignment indicated that cross-cultural motivation and psychological empowerment related positively to initial levels of adjustment, and indirectly and negatively to work adjustment change. Challenge stressors positively related to changes in work adjustment over time. In turn, changes in work adjustment significantly related to expatriates' assignment satisfaction and premature return intention, explaining variance above and beyond that explained by average levels of work adjustment. These findings extend understanding of how and why expatriate work adjustment evolves over time, as well as the unique influence that differences in adjustment change have on important expatriate outcomes.